PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI SMA KATOLIK KARITAS TOMOHON PADA MATERI KIMIA UNSUR - Balangasan, Meylisa; Karundeng, Marlina; Saiya, Abdon (LPPM Politeknik Saint Paul Sorong, 2025)
This study aims to test the feasibility of Android-based learning media using the Problem Based Learning (PBL) model on elemental chemistry material at Karitas Tomohon Catholic High School. This research is motivated by the lack of use of technology as a learning media in schools making students less interested in learning that is still monotonous (conventional) and less interesting. The research method used is research and development (R&D) with reference to the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this research were chemistry teachers and students of class XII, especially class XII-A. Validation was conducted by media experts and material experts to ensure the feasibility and quality of the application. The results showed that the android-based learning media developed was very feasible with a percentage of 80% from media experts and 92% from material experts. The subject teacher's response gave a feasibility level with a percentage of 100% and student responses with a percentage of 87.78% so that it was declared very feasible as a learning media. The conclusion of this research is that android-based learning media with PBL model is effectively used in learning Chemistry Elements in high school. This media can be an innovative solution in utilizing technology to improve the quality of education.